PENGARUH KEBIJAKAN HUTANG, PROFITABILITAS, LIKUIDITAS, DAN KESEMPATAN INVESTASI TERHADAP KEBIJAKAN DIVIDEN - Putri, Ayu Rahmania; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the influence of debt policy (which is proxy by Debt to Asset Ratio), profitability (which is proxy by Return on Asset), liquidity (which is proxy by Current Ratio), and investment opportunity (which is proxy by Price Earnings Ratio) to the dividend policy (which is proxy by Dividend Payout Ratio). The population is all companies which are engaged in the field of property and real estate sub sector which are listed in Indonesia Stock Exchange (IDX). The research data is the secondary data which has been obtained from Indonesia Stock Exchange and www.idx.co.id. That is the financial statement in five years in 2011-2015 periods. The research samplesare 10 companies which have been selected by using purposive sampling and the hypothesis test has been carried out by using Multiple Linear Regressions analysis. The result of the hypothesis test shows that: (1) liquidity and investment opportunity give positive influence to the dividend policy. (2) Debt policy and profitability does not give any influence to the dividend policy. Keywords: Debt policy, profitability, liquidity, investment opportunity, dividend policy.